2014
DOI: 10.1039/c4cy00418c
|View full text |Cite
|
Sign up to set email alerts
|

Efficient asymmetric hydrogenation of quinolines in neat water catalyzed by chiral cationic Ru-diamine complexes

Abstract: The first highly effective and enantioselective hydrogenation of quinolines catalyzed by chiral cationic Ru-diamine complexes in undegassed water was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 72 publications
2
15
0
Order By: Relevance
“…Cationic chiral N –sulfonylated diamine functionalized organometallic complexes, a type of catalytically efficient active species for asymmetric transfer hydrogenation (ATH) reaction, have obvious superiority in catalytic process with respect to their corresponding neutral ones since cationic complexes as real active species based on mechanism study could significantly favor asymmetric transfer hydrogenation process of ketones especially in an aqueous medium (Noyori and Hashiguchi, 1997 ; Liu et al, 2004a , b ; Gladiali and Alberico, 2006 ; Wu et al, 2006 , 2008 ; Ikariya and Blacker, 2007 ; Ohkuma et al, 2007 ; Wang et al, 2008 , 2011 , 2013b ; Ding et al, 2013 ; Yang et al, 2014 , 2016 ; Zhang et al, 2015 ). Therefore, direct immobilization of cationic ruthenium active species within the FDU−12 is beneficial to enhance ATH transformation.…”
Section: Resultsmentioning
confidence: 99%
“…Cationic chiral N –sulfonylated diamine functionalized organometallic complexes, a type of catalytically efficient active species for asymmetric transfer hydrogenation (ATH) reaction, have obvious superiority in catalytic process with respect to their corresponding neutral ones since cationic complexes as real active species based on mechanism study could significantly favor asymmetric transfer hydrogenation process of ketones especially in an aqueous medium (Noyori and Hashiguchi, 1997 ; Liu et al, 2004a , b ; Gladiali and Alberico, 2006 ; Wu et al, 2006 , 2008 ; Ikariya and Blacker, 2007 ; Ohkuma et al, 2007 ; Wang et al, 2008 , 2011 , 2013b ; Ding et al, 2013 ; Yang et al, 2014 , 2016 ; Zhang et al, 2015 ). Therefore, direct immobilization of cationic ruthenium active species within the FDU−12 is beneficial to enhance ATH transformation.…”
Section: Resultsmentioning
confidence: 99%
“…The most convenient route to chiral tetrahydroquinolines is the asymmetric reduction of quinolines. In continuing our research into ATH, we found that the protocol developed for highly efficient reduction of ketones could also been applied to ATH of cyclic C=N bonds with a slight modification of the tosylated diamine ligand and adjusting the solution pH 39,40…”
Section: Th With Noyori–ikariya‐type Catalysts In Watermentioning
confidence: 99%
“…Water has been applied as reaction media catalyzed by chiral Ru‐diamine complexes as described in 2014 [61].…”
Section: The Strategies For Hydrogenationmentioning
confidence: 99%